1) b = 10
2) y = 2
3) y = 1,2
Пошаговое объяснение:
1) 15 : b = 3 : 2
Методом пропорции
3 * b = 15 * 2
3b = 30
b = 30 : 3
b = 10
2) 3 : 21 = y : 14
21 * y = 3 * 14
21y = 42
y = 42 : 21
y = 2
3) y : 2,4 = 3 : 6
6 * y = 2,4 * 3
6y = 7,2
y = 7,2 : 6
y = 1,2
1) b = 10
2) y = 2
3) y = 1,2
Пошаговое объяснение:
1) 15 : b = 3 : 2
Методом пропорции
3 * b = 15 * 2
3b = 30
b = 30 : 3
b = 10
2) 3 : 21 = y : 14
Методом пропорции
21 * y = 3 * 14
21y = 42
y = 42 : 21
y = 2
3) y : 2,4 = 3 : 6
Методом пропорции
6 * y = 2,4 * 3
6y = 7,2
y = 7,2 : 6
y = 1,2